Optimization of Performance and Emission Characteristics of Diesel Engine with Biodiesel Using Grey-Taguchi Method - Goutam Pohit; Dipten Misra (Journal of Engineering)
Engine performances and emission characteristics of Karanja oil methyl ester blended with diesel were carried out on a variable compression diesel engine. In order to search for the optimal process response through a limited number of experiment runs, application of Taguchi method in combination with grey relational analysis had been applied for solving a multiple response optimization problem. Using grey relational grade and signal-to-noise ratio as a performance index, a particular combination of input parameters was predicted so as to achieve optimum response characteristics. It was observed that a blend of fifty percent was most suitable for use in a diesel engine without significantly affecting the engine performance and emissions characteristics.